Etika Komunikasi Bisnis dalam Al-Qur'an - M. Ibnu Naufal Maskuri (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2022)
Researchers here want to know the regulations of business regulations in running a business based on the verses of the Koran. The principle of business communication regulation is a boundary, a reference, a method in which the continuity of the business process occurs. Regarding what is allowed and not allowed when running a business, the regulation of business communication principles is a sign for business people. The purpose of this study is to see and understand the importance of the principles of business communication in the verses of the Koran. for the method used is a library research technique by conducting a library search of written materials, either in the form of notes, books or previous research. The quotations in this study are sourced from the professional point of view of experts and previous research that has been carried out and explains the principles of business communication regulation. The result of this research is that in running a business, it is necessary to have regulations on the principles of existing business communication, so that business ventures are blessed, smooth, and get the blessing of Allah SWT. The principles of business communication regulation are recorded in the verses of the Koran, including the principles of business communication regulation of qaulan sadida, qaulan zura, qaulan maisura, and qaulan layyina. For this reason, Prophet Muhammad SAW became a role model in carrying out business communication regulations, such as customer orientation and transparency.